2016
DOI: 10.1115/1.4034525
|View full text |Cite
|
Sign up to set email alerts
|

The Wingtip Vortex of a Dimpled Wing With an Endplate

Abstract: Dimples used as sub-boundary layer vortex generators have been shown to reduce wake size at large angles of incidence. The effect these dimples have on wingtip vortices with an endplate is measured via laser Doppler anemometry (LDA) on an inverted Tyrrell026 airfoil (ReC = 0.5 × 105 and chord = 0.075 m) in ground effect in order to determine the flow characteristics for this configuration and to see if previous measurements were performed in a thinner part of the wake due to any potential wake waviness. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Since then, several attempts have been made to investigate the effect of endplates on wing performance. Beves et al [63] carried out an experimental study on the effect of a rectangular endplate (95 mm × 45 mm) mounted on an inverted Tyrrell026 airfoil with a chord length of 0.075 m at a chord-based Reynolds number Re c = 0.5 × 10 5 . They found that the rectangular endplates inhibit spillage flow at the wingtip, thus maintaining a pressure difference between the upper and lower surfaces.…”
Section: Endplatesmentioning
confidence: 99%
“…Since then, several attempts have been made to investigate the effect of endplates on wing performance. Beves et al [63] carried out an experimental study on the effect of a rectangular endplate (95 mm × 45 mm) mounted on an inverted Tyrrell026 airfoil with a chord length of 0.075 m at a chord-based Reynolds number Re c = 0.5 × 10 5 . They found that the rectangular endplates inhibit spillage flow at the wingtip, thus maintaining a pressure difference between the upper and lower surfaces.…”
Section: Endplatesmentioning
confidence: 99%